(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2021)
Smallholder farmers influenced from the challenges of production constraints to afford farm family with surplus food. To improve this problem the present study was designed to evaluate legume shrubs hedgerow intercropping with maize. In the present study, the growth performance of Sesbania sesban and Cajanus cajan was evaluated to determine their potential in hedgerow intercropping. The result revealed that Sesbania sesban performs better than Cajanus cajan in terms of biomass provision in the successive pruning, mean height, branching, diameter at breast height and root collar diameter. Biomass produced from Sesbania sesban was significantly higher than Cajanus cajan, this plays great role in soil nutrient improvement and maize yield also increased. There was an increasing trend in soil properties in terms of organic C, total N, in legume treatments especially in Sesbania sesban hedgerow to the initial and control soils. Maize grain yield higher under Sesbania sesban hedgerow plot than Cajanus cajan, maize with fertilizer and control. This should be intensively demonstrated to sustain the agricultural production as an organic farming through integration of easily adapting, less competing with the companion crop, deep rooted and fast growing legume tree/shrub species. Further research is important in areas of determining decomposing rate of different parts, pruned biomass and potential species should be identified. Int. J. Agril. Res. Innov. Tech. 11(1): 60-68, June 2021